Vera Bushwack - Burwash, Sig (Drawn & Quarterly, 2024)
A uniquely thrilling and emotive fantasy ride along a sea-bordered highway. The wondrous rustic landscape of Nova Scotia bursts from the page in Vera Bushwack, where reality gladly gives way to fantastical flights of fancy before gently coming back down to earth. A chainsaw fires up and Drew’s vision blurs. Their body vibrates alive with the whrrr of the engine, the whiff of gas. Drew dissolves as their alter-ego, Vera Bushwack, takes charge. Assless-chaps-wearing, unflinching Vera slashes through thick trunks, felling trees righteously from the back of a majestic steed. Vera’s here to help, of course. Drew needs to clear the land for their future cabin in the woods. And if it weren’t for Vera’s brazenness, Drew may, ironically, fall reliant on others to learn self-reliance. Nevertheless, men enter Drew’s orbit, all too eager to explain how things work—an aggravating occurrence that comes crashing into Drew as dependably as the nearby ocean waves. Joy, anger, grief, and self-acceptance ripple through these pages with Sig Burwash’s hilariously expressive pencil drawings and flair for buoyant watercolors. Approaching something like liberation, our protagonist comes to terms with past traumas, boundaries, and the many expressions of themself.